2019
DOI: 10.1186/s13104-019-4786-y
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional deficiency and associated factors among new pulmonary tuberculosis patients of Bale Zone Hospitals, southeast Ethiopia

Abstract: ObjectiveTuberculosis remains deadliest communicable diseases accountable for health problem among various individuals annually and is related to malnutrition. Addressing nutritional deficiency in Tuberculosis patients is a crucial side of tuberculosis management programme. Therefore, the aim was to assess the magnitude of nutritional deficiency and associated factors among new pulmonary tuberculosis patients of Bale Zone Hospitals, south-east Ethiopia, 2018. Cross-sectional study design was utilized. Data col… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 18 publications
(20 reference statements)
1
5
1
Order By: Relevance
“…Two studies in Ethiopia have also reported higher rates of concurrent undernutrition among adult patients with TB (57.2%) 29 and (63.2%) 30 which again are higher than we report. This could be due to the high number of participants from rural areas, where there may be less access to health care and nutrition-rich food.…”
Section: Discussioncontrasting
confidence: 74%
“…Two studies in Ethiopia have also reported higher rates of concurrent undernutrition among adult patients with TB (57.2%) 29 and (63.2%) 30 which again are higher than we report. This could be due to the high number of participants from rural areas, where there may be less access to health care and nutrition-rich food.…”
Section: Discussioncontrasting
confidence: 74%
“…Participants with cHIV/TB had the lowest BMI, which could be attributed to nutritional deficiency due to TB infection. Nutritional deficiency, resulting in low BMI, was found to be high in pulmonary TB patients [34], while an overweight BMI is shown to significantly reduce risk for TB [35].…”
Section: Discussionmentioning
confidence: 99%
“…(Mirlohi, Ekrami, Shirali, Ghobeishavi, & Pourmotahari, 2016) and 57 people (55.88%) TB patients were underweight (BMI <18.5). (Hussien, Hussen, Seid, & Hussen, 2019) Research by Fariz Muaz (2014) stated that there was a relationship between nutritional status and the incidence of pulmonary tuberculosis. It can be understood that in general, malnutrition will weaken the immune system against disease, so that a person with poor nutritional status will be more likely to suffer from tuberculosis.…”
Section: Discussionmentioning
confidence: 99%